The use of a Virtual Learning Environment (VLE) to embed library information services in a Blended Learning Environment (BLE) : a University of Pretoria Engineering study - Van Deventer, Martie (University of Pretoria, 2019)
Mini Dissertation (MIT)--University of Pretoria, 2018.